Friedrich Schiller collection, 1883-1941. - Schiller, Friedrich, 1759-1805.
English translations of two of Schiller's works: Kabale und Liebe (Love and Intrigue), translated by John Howard Payne, and Die Sendung Moses (The Mission of Moses), translated by Emile B. Skraly. Also includes newspaper clipping (1941) regarding Adolf Hitler's choice of Rudolf Hesse as his successor as head of the Nazi Party.
Dramatist and poet.
Collection material in German, with English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hess, Rudolf, -- 1894-1987.; Hitler, Adolf, -- 1889-1945.; Payne, John Howard, -- 1791-1852.; Schiller, Friedrich, -- 1759-1805 -- Translations into English; Skraly, Emile B; Nationalsozialistische Deutsche Arbeiter-Partei.; Dramatists; Poets